EVALUATING THE IMPACT OF CHATGPT IMPLEMENTATION ON HR PERFORMANCE SKILLS: A CASE STUDY OF ACADEMIC INSTITUTIONS IN OMAN - Shannaq, Boumedyen; Alabri, Ahmed (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Academic institutions increasingly integrate AI-driven tools like ChatGPT to enhance HR performance. However, the effectiveness of such adoption depends on various factors. The study investigates the impact of ChatGPT implementation on HR performance skills in Omani academic institutions, with user training, system usability, and cultural factors as moderating variables. Using a structured questionnaire, this study employs survey data collected from 791 HR staff from five academic institutions. Structural Equation Modeling (SEM) was used to examine direct and indirect relationships within the proposed framework and test the conceptual model. The outcomes show that implementing ChatGPT enhances the performance of HR skills predictably (B = 0.092, P = 0.003). User training showed a partial mediation effect (B = 0.090, t = 4.615, P = 0.000), which is evident as a key facilitator of the relationship between ChatGPT adoption and HR outcomes. In the same way, system usability was found to have a lesser but significant partial mediation effect (B = 0.019, t = 1.715, P = 0.043). However, organizational culture did not moderate the relationship significantly, B = 0.005, t = 0.922, P = 0.178. The findings of this study suggest that integrating AI-enabled tools like ChatGPT in academic HR settings requires a user-centered system development approach and targeted training. The results contribute to the literature by establishing a theoretical foundation for understanding how technology applications influence institutional efficiency and goal attainment, particularly in regions where education significantly impacts socio-economic development. JEL Classification Codes: G32, F65, L66, L25, M41.